Military aid, direct intervention and counterterrorism - María D. C. García-Alonso; Paul Levine; Ron Smith (University of Kent, School of Economics, 2015)
We present a model of transnational terrorism where two countries, home and foreign, face a terrorist threat based in the foreign country. The home country chooses how much to invest in defending itself or in reducing terrorist resources either indirectly by subsidising the foreign country or by directly by intervening itself. We use backward induction to solve a multiple stage game where the home country first commits to its policy decisions, then the foreign country chooses the effort it expends on reducing terrorist capability and finally, the terrorists decide their effort in attacking in the home or foreign country. In a numerical solution of the calibrated model, direct intervention only arises in equilibrium if foreign and home efforts are not close substitutes in the technology used to reduce the resources of the terrorist group. Greater relative military efficiency in the home country makes intervention more likely.
Keywords: D58; D74; H40; 330; military conflict; strategic delegation; counterterrorism